Synthesis and anticancer activity of novel 9, 13-disubstituted berberine derivatives. Issue 2 (15th January 2020) - Wang, Zhi-Cheng; Wang, Jing; Chen, Huang; Tang, Jie; Bian, Ai-Wu; Liu, Ting; Yu, Li-Fang; Yi, Zhengfang; Yang, Fan
Graphical abstract: Abstract: Novel berberine derivatives with disubstituents on positions C9 and C13 were synthesized and evaluated for antiproliferative activities against human prostate cancer cell lines (PC3 and DU145), breast cancer cell line (MDA-MB-231) and human colon cancer cell lines (HT29 and HCT116). All compounds showed significantly enhanced antiproliferative activities compared with berberine. Notably, compound 18e exhibited the strongest cytotoxicity against PC3 cells with an IC50 value of 0.19 μM, and the highest selectivity index (SI PC3  > 20). Further studies showed that 18e could arrest the cell cycle at G1 phase, and significantly inhibit tumor cell colony forming and migration even at low concentrations. Interestingly, 18e could significantly induce cytoplasmic vacuolation, suggesting a different mode of action from berberine.